Implementasi Metode K-Nearest Neighbor untuk Rekomendasi Keminatan Studi (Studi Kasus: Jurusan Teknik Informatika Universitas Brawijaya) - Luthfi Anshori; Rekyan Regasari Mardi Putri; Tibyani Tibyani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
The Informatics Engineering Programme in Brawijaya University has 5 (five) interests that should be taken by each students in their course period. Considering the importance of this interests to students' academic process which later will affect their final project until their graduation, therefore students are expected to choose their insterests based on their attentiveness and ability. Based on the Faculty of Computer Science Handbook Universitas Brawijaya 2016, there are 5 (five) interests existing in Informatics Programme, namely Software Engineering, Smart Computing, Mobile devices, Computer Networks and Games. In order for students to choose the right interest then they need a recommendation system for students so that students can choose interest that suites their talent, desire and scores of courses that have been taken. By implementing K-Nearest Neighbor method which aims to give recommendation of interests based on attribute of compulsory courses scores. Testing is done by comparing the results of the interests that has been verified by campus' academic with the results of the system. From the test of data train as much as 30 data of students which have chosen their interests hence gotten the result of accuracy as much 76.66% to trainned data with the most optimal K value, the K value 10, therefore can be concluded this recommendation of interest system can help student give recommendation of interest which will be chosen.